Analysis of quality characteristics and feasibility study of dish soap form the fruit peel extract - Wardhana, Danu Indra; Aulia, Anisa Nurina; Setiawan, Andika Putra; Nalawati, Ara Nugrahayu; Syafia, Fina; Rosa, Firlana (AGROMIX, 2024)
Introduction: Fruit peel is one of the natural ingredients that has not been optimally utilized and can be used as a raw material for making dish soap because it has antibiotic, antiseptic, and antibacterial content. This study aims to make dish soap using dragon fruit peel extract, papaya fruit, and banana fruit as natural ingredients and determine the quality characteristics of dish soap and business feasibility analysis. Methods: This research was conducted in two stages. The first stage selected the best fruit skin dish soap based on the quality characteristics and organoleptic tests on the product. The second stage then analyzed the business feasibility of the best fruit peel extract dish soap product. Results: The quality characteristics of dragon fruit peel, banana, and papaya skin extract dish soap with pH test parameters, FFA content, and free alkali content are in accordance with SNI standards, but the viscosity test shows that it is not suitable and has a value below SNI, and the results of the organoleptic test show that dragon fruit peel extract dish soap is preferred by panelists compared to banana and papaya skin extract soap with an average value of 4.3 color parameters; aroma 3.5; texture 3.6; and overall 4.1. Conclusion: Dragon fruit peel extract dish soap has the best organoleptic test value compared to banana and papaya peel dish soap. The results of the feasibility study analysis of the dragon fruit peel extract dish soap business have a BEP Unit value of 31, BEP Rupiah of IDR.462,185, ROI of 81.64%, and R / C of 1.82 where this business is considered feasible if developed.